2007
DOI: 10.1183/09031936.00095406
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of incremental and constant load tests of inspiratory muscle endurance in COPD

Abstract: The aim of the present study was to determine the relative value of incremental and constant load tests in detecting changes in inspiratory muscle endurance following high-intensity inspiratory muscle training (H-IMT) in chronic obstructive pulmonary disease.In total, 16 subjects (11 males; forced expiratory volume in one second (FEV1) 37.4¡12.5%) underwent H-IMT. In addition, 17 subjects (11 males; FEV1 36.5¡11.5%) underwent sham inspiratory muscle training (S-IMT). Training took place three times a week for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 34 publications
2
40
0
8
Order By: Relevance
“…As for the endurance test, it was noticed that only sustained maximum inspiratory pressure was significantly different between the groups, which corroborates the results of Hill et al, 21 who concluded that sustained maximum inspiratory pressure is more sensitive to detect differences in the endurance of those who undergo inspiratory muscle training. That is because the time limit is highly variable among subjects, and it can be influenced by many external factors, such as motivation, tolerance of unpleasant sensations, and the very strength and endurance of inspiratory muscles.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…As for the endurance test, it was noticed that only sustained maximum inspiratory pressure was significantly different between the groups, which corroborates the results of Hill et al, 21 who concluded that sustained maximum inspiratory pressure is more sensitive to detect differences in the endurance of those who undergo inspiratory muscle training. That is because the time limit is highly variable among subjects, and it can be influenced by many external factors, such as motivation, tolerance of unpleasant sensations, and the very strength and endurance of inspiratory muscles.…”
Section: Discussionsupporting
confidence: 80%
“…The breathing pattern was kept free. This protocol is an adaptation of the protocols of Hill et al 21 and Beckerman et al 32 The calisthenics-and-breathing exercises group performed a program of specific exercises aimed at improving biomechanics and chest mobility, adapted from the program described by Probst et al 11 The sequence of exercises was designed so that the complexity progressively increased every month. A series of 9 exercises, each one performed 15 times, was carried out (Table 1).…”
Section: Physical Training Programmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that with COPD patients, the advantages of rehabilitation depend on the training intensity used (Hsieh et al, 2007). Thus far, most studies utilize inspiratory muscle training to rehabilitate COPD patients (Hill et al, 2007). Potentially, HIT may be a useful alternative training approach.…”
Section: Future Directionsmentioning
confidence: 99%